Two new species of Dendrobium Sect. Calcarifera (Orchidaceae) from Terengganu, Peninsular Malaysia - Besi, Edward Entalai; Nikong, Dome; Mustafa, Muskhazli; Go, Rusea (Malaysian Nature Society, 2018)
Two new species, Dendrobium ainiae R. Go et E. E. Besi and Dendrobium ruseae E. E. Besi et Dome belonging to Sect. Calcarifera are described and illustrated from Terengganu, Peninsular Malaysia. These species are so far known from a population in lowland dipterocarp forest. A field key to the Peninsular Malaysian taxa of Dendrobium Sect. Calcarifera including Dendrobium chewiorum is also provided.